IMPROVING THE STUDENTS’ PERFORMANCE FROM THE EXPECTATION AND QUALITY OF LEARNING - Khusaini Khusaini; Ali Sandy Mulya (Assets: Jurnal Akuntansi dan Pendidikan, 2021)
ABSTRACTThis research aims to measure expectations, gender, learning quality, and control variables on the performance of the undergraduate program of Accounting at Tangerang Municipality. The target population is 1,898 students, with 331 of them becoming the sample. The sampling technique was Disproportionate Random Sampling and used a Binary Probit Regression. The distribution of the questionnaires used a Google Form. The results showed that the expectations and quality of learning had a significant effect on improving performance. On the other hand, gender was insignificant. This study's findings contribute to universities always maintaining student expectations and the quality of learning so that graduates have good performance.ABSTRAKPenelitian ini bertujuan untuk menguji harapan, gender, kualitas pembelajaran, dan variabel kontrol terhadap kinerja mahasiswa program sarjana S-1 Akuntansi di Perguruan Tinggi Kota Tangerang. Populasi sebanyak 1.898 mahasiswa dan ukuran sampel sebanyak 331 sampel. Teknik sampling adalah disproportionate random sampling dan menggunakan analisis binary probit regression. Distribusi kuesioner menggunakan google form. Hasil penelitian menunjukkan bahwa harapan dan kualitas pembelajaran berpengaruh signifikan terhadap peningkatan kinerja mahasiswa, sebaliknya gender tidak signifikan. Temuan penelitian ini memberikan konstribusi kepada perguruan tinggi untuk selalu menjaga ekspektasi mahasiswa dan mutu pembelajaran agar para lulusannya memiliki kinerja yang baik.